1933 Haw. Sess. Laws 36 - (:unkn) unknown (My University, 1933)
An Act Regulating the Sale, Transfer, and Possession of Firearms and Ammunition, § 2: Defined firearms as a weapon whose operating force is an explosive. The definition includes pistols, revolvers, rifles, shotguns, machine guns, automatic rifles, noxious gas projectors, mortars, bombs, cannon, and sub-machine guns. Defined crime of violence as murder, manslaughter, rape, kidnapping, robbery, burglary, and crimes labeled in Revised Laws § 4130-4131. Pistol and revolver are defined as a firearm with a barrel less than twelve inches in length and capable of discharging loaded ammunition or noxious gas.
Keywords: DEFINITIONS